Indication and Clinical Outcomes of Percutaneous Endoscopic Gastrostomy: A Single-center Retrospective Analysis - Ju Sung Sim; Seoung Young Kim; Ye Jin Lee; Ji Hye Seo; Dong Ju Kim; Jung Wan Choe; Dongwon Lee; Sung Woo Jung; Sang Woo Lee (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Background/Aims: Percutaneous endoscopic gastrostomy (PEG) is performed to provide enteral nutrition to patients who require tube-feeding support due to impaired oral intake. As life expectancy increases, the need for, and use of PEG also tend to increase. We aimed to evaluate the indications and complications of PEG insertion, and to investigate any differences in the complication group. Materials and Methods: We conducted a retrospective analysis of 109 patients who received a PEG procedure between April 2011 and April 2016 in the Korea University Ansan Hospital. We reviewed the indications and complications related to PEG insertion and time interval of tube change. Results: Among 109 patients who underwent a PEG procedure, 71.6% were male, and the mean age was 68.2 years. The most common indications for PEG were central nervous system diseases, including stroke (33.9%), cerebral hemorrhage (29.4%), and hypoxic brain damage (8.3%). The overall complication rate was 14.7%, and the most common complication was peristomal infection (7.3%). Most of the complications occurred within 10 days in 14 of 16 patients (87.5%). The patients with complications were older than those without complications (74.6±11.1 vs. 67.1±14.0 years, P=0.043). The mean time interval for gastrostomy tube change was 7.3 months. Conclusions: The most common indication of PEG was brain disease, and the complication rate cannot be ignored. Careful attention is needed after a PEG procedure especially in elderly patients.